"Poles of the World Unite": The Transnational History of the 1929 World Congress of Poles Abroad in the Context of Interwar Soviet–Polish Rivalries. Issue 6 (6th November 2022) - Palko, Olena
Abstract: By investigating the information and propaganda campaign surrounding the election of delegates to the 1929 World Congress of Poles Abroad, this article seeks to elucidate a complex interplay between foreign policy considerations, security concerns, and nationality policies of the Polish and Soviet governments. It examines the role of national minorities in the Soviet modernization effort and the ongoing Polish-Soviet rivalry of the interwar period. The focused study of the information campaign, and the public discussion surrounding the election process to the congress, contributes also to the debates on mass political culture in the interwar Soviet Union. Party communication, intelligence, and secret reports compiled during the local elections and conferences provide a unique source for sampling public opinion of the Polish population regarding the Soviet regime in the early years of Stalin's First Five-Year plan. The article argues that despite the considerable efforts of the party to define and promote Polish identity, and thus shift their loyalties closer to the Soviet state, the Polish population in Soviet Ukraine, even at the end of the 1920s, continued to express persistent nonconformity and a lack of faith in the Soviet government.